Connecting and Change in African Societies: Examples of "Ethnographies of Linking" in Anthropology - de Bruijn, Mirjam; van Dijk, Rijk (Anthropologica, 2022)
Africa has been witnessing rapid changes in the social landscape over the past ten years. Processes of globalization and the advancement of new technologies have been impacting on local social networks significantly. This paper moves away from an analysis of networks as defining social space, towards an ethnography of linking and connections. What does the link ing entail and how does this encompass moments of change? We consider two linking technologies of different natures—the mobile phone and the passport-to-life—and assess what these technologies link. Central in this analysis is how linking con nections possess agency in producing social change.